Diagnostic Contexts of Echocardiographic Nonapical Window - Paolo Springhetti, MD; Giovanni Benfari, MD, PhD; Stefano Nistri, MD, PhD; Elena Maria Santina Jannello, MD; Giulia Elena Mandoli, MD; Luigi Badano, MD, PhD; Flavio Luciano Ribichini, MD; Denisa Muraru, MD, PhD (JACC: Case Reports, 2024)
The long-established utility of multiwindow interrogation in echocardiography (suprasternal notch, right and left sternal border, apex, and subxiphoid) is sometimes not systematically implemented in routine practice. This case series emphasizes the pivotal importance of such practice for the systematic assessment of aortic valve stenosis and in the evaluation of left ventricular outflow tract and the aorta.